Pluralistic Fiqh Based on Perspective of Imam Al-Sya’rani in the Book of al-Mizan al-Kubra - Ahmad Taufik Hidayat; Alfurqan Alfurqan (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2020)
This research was intended to examine al-Sya’rani main thoughts on the diversity of legal schools as outlined in his al-Mizân al-Kubrâ work along with the context and challenges historically which in many cases gave rise to ikhtilaf (differences of opinion) in Fikih, as well as an overview in the legal context as a means of social transformation. The method used in this study was library research, both primary and secondary. Primary sources consisted of the works of al-Sya’rani (especially al-Mizan al-Kubra) with more emphasis on the content analysis. In detail, the problem is formulated in some questions; (1) what is the socio-historical situation (political, socio economic, intellectual, and religious traditions) behind the formation of al-Sya’rani ideas about Fikih pluralistic?, (2) what is the construction or pattern of al-Sya’rani thought regarding pluralistic Fikih?, (3) what is the position of al-Sya’rani thought in the perspective of law as one of the means of social transformation? As a result of this discussion, al-Sya’rani seeks to provide a new orientation in legal thinking in a direction that is closer to the demands of a real and pluralistic reality of life. The idea is then outlined in four main points of view which include: (1) Justification of three episteme systems (2) The use of pragmatism principles in the application of the law, Legitimacy of legal changes in line with the development of the situation (3) His views on the necessity of ijtihâd and prohibition of taqlîd in practice Sharia law.